Immunohistochemical Analysis of Leucocyte Subsets in the Sinonasal Mucosa of Cats with Upper Respiratory Tract Aspergillosis. Issue 2 (August 2016) - Whitney, J.L.; Krockenberger, M.B.; Day, M.J.; Beatty, J.A.; Dhand, N.K.; Barrs, V.R.
Summary: Leucocyte populations in the sinonasal mucosa of cats with and without upper respiratory tract aspergillosis were compared using immunohistochemistry and computer-aided morphometry. Inflammation was identified in the nasal mucosa of all affected cats, comprising predominantly of lymphoplasmacytic infiltration of the lamina propria associated with epithelial proliferation and degeneration. There was intense and diffuse expression of class II antigens of the major histocompatibility complex, associated with sites of hyphal invasion with hyperplasia and ulceration of the epithelium adjacent to fungal elements. Significantly more CD79b + cells, total lymphocytes, immunoglobulin (Ig)-expressing cells and MAC387 + cells infiltrated the epithelium and more IgG + cells and total Ig-expressing cells infiltrated the lamina propria in affected cats compared with controls. Importantly, the inflammatory profile in affected cats was not consistent with the T helper (Th)1 and Th17 cell-mediated response that confers protective acquired immunity against invasive aspergillosis in dogs and people and in murine models of the infection. This finding may help to explain the development of invasive aspergillosis in systemically immunocompetent cats.